History of the Catholic Church from the Renaissance to the French Revolution $1 (BVolume 1s - MacCaffrey, James, 1875-1935 (Salt Lake City, UT : Project Gutenberg, 2000)
"History of the Catholic Church from the Renaissance to the French Revolution" by Rev. James MacCaffrey is a historical account written in the early 20th century. The work explores the complexities and transformations of the Catholic Church during a pivotal period marked by intellectual, cultural, and political upheaval, spanning from the Renaissance through the tumultuous events of the French Revolution. It aims to provide a thorough understanding of the religious, social, and political contexts that shaped the Church's evolution in this era, addressing influential figures like Martin Luther and the Reformation movement alongside the responses of the Church itself. The opening of the work lays the groundwork for an exploration of the Reformation by highlighting the prevailing tension between the traditional doctrines of the Catholic Church and the rising philosophies of Humanism and individualism during the Renaissance. It outlines a historical shift from the ideals of the Middle Ages to those of modernity, characterized by increasing secularism and challenges posed to established doctrines. Additionally, it introduces the intellectual struggles marked by the competing values of classical culture and Scholastic philosophy, setting the stage for a detailed analysis of the Reformation's religious and political implications as it unfolds throughout the subsequent chapters. (This is an automatically generated summary.)
Release date is 2000-11-01
Keywords: Catholic Church -- History -- Modern period, 1500-